Nutrient Digestibility in Goats Fed With Corn Fodder Supplemented With Palm Kernel Meal - Austral Jr, Tomas M.; Bantugan, Sulpecio C. (Annals of Tropical Research, 2016)
Sixteen (16) goats were randomly distributed to the four dietary treatments to determine their nutrient digestibility which constituted four treatment combinations – commercial cultivar of white corn variety, F1 Taiwanese corn fresh fodder, F1 Taiwanese corn fresh fodder + 0% palm kernel meal in mixed concentrate , and F1 Taiwanese corn fresh fodder + 30% palm kernel meal in mixed concentrate. These were randomized in a complete block design using SPSS Version 11.5 or Windows. Tukey test (Honestly Significant Difference) was used to test the significant differences among treatment means. Results revealed highly significant differences in terms of dry matter intake, organic matter intake, organic matter digestibility, and apparent digestible energy. Observed results were attributed to better nutrient digestibility due to its rumen fermentation and micro-organism activity. Based on the results of the study, use of corn fodder (65-75 days after planting) and inclusion of 30% palm kernel meal in the diet are recommended since it improved nutrient digestibility, increased feed intake, and energy values compared to use of corn fodder alone. However, it is recommended that optimum level of palm kernel meal usage be further studied to measure the level of efficiency and nutrient digestibility in goats.